Managing new-onset atrial fibrillation in critically ill patients: a systematic narrative review - O'Bryan, LJ; Redfern, OC; Bedford, J; Petrinic, T; Young, JD; Watkinson, P (BMJ Publishing Group, 2020)
Objectives: The aim of this review is to summarise the latest evidence on efficacy and safety of treatments for new-onset atrial fibrillation (NOAF) in critical illness.